The electronic structure and spin–orbit-induced spin splitting in antimonene with vacancy defects. Issue 70 (12th July 2016) - Yang, Lifang; Song, Yan; Mi, Wenbo; Wang, Xiaocha
Abstract : We study the geometric, electronic properties, and spin splitting in monovacancy (MV) and divacancy (DV) antimonene with five different models using first-principles calculations. Abstract : We study the geometric, electronic properties, and spin splitting in monovacancy (MV) and divacancy (DV) antimonene with five different models using first-principles calculations. Meanwhile the influence of spin–orbit coupling (SOC) is included. Different vacancies cause different geometric structures with or without inversion symmetry and influence the electronic structures. MV antimonene shows metallic character, however, four DV antimnoene models preserve the semiconducting character narrowing the band gap. The inversion asymmetry and SOC lead to the spin splitting in MV and two DV models. Zeeman-type spin splitting appears with out-of-plane spin polarization along M – K – Γ . Rashba and Dresselhaus effects induced spin splitting occurs at Γ and M points in MV.